Characteristics Of Fish Nugget with Tapioca Flour and Carrot Flour (Daucus carota L): Karakteristik Naget Ikan dengan Bahan Pengisi Tepung Tapioka dan Tepung Wortel (Daucus carota L) - Prischilla G A Rera Rejerusalem; Vivi Nuraini; Merkuria Karyantina (Fakultas Sains dan Teknologi Unisri, 2024)
Nugget is processed mashed meat. Several types of fish such as tuna, tilapia, and snapper have the potential to increase sales value and can be used as raw material for nuggets, because apart from having quite high proteins, they also have thick flesh. Carrot flour has high levels of fiber and also high levels of beta-carotene. The purpose of this study was to determine the characteristics of fish nuggets which were high in fiber and beta-carotene with variations in the addition of carrot flour, tapioca flour and to find out the highest level of preference for fish nuggets. research using a completely randomized design (CRD) 2 factors with a comparison of carrot flour and tapioca flour and variations of fish species. The best chemical test results were the comparison of carrot flour: tapioca flour (40%:20%) with tuna fish with beta-carotene content of 6.69 Î¼g/g, crude fiber content of 36.54%. The highest preference sensory test result is the comparison of carrot flour with tapioca flour (40%: 20%) with the type of tilapia meat with a color test result of 3.14 (likes), taste test 3.18 (likes), aroma test 3.20 (likes), texture test 3.29 (likes), and overall preference test 3.82 (likes). ). Fish nuggets made from tapioca flour and carrot flour can be a food that has high levels of crude fiber and beta-carotene.